The effect of animal husbandry on economic growth: Evidence from 13 provinces of North China - Wang, Chu; Zhang, Jinbing; Zhou, Wenneng (Frontiers in Environmental Science, 2023)
Promoting animal husbandry industry is important to help strengthen the agricultural sector. Based on an exploratory spatial analysis, spatial econometric model, and geographically weighted regression (GWR) model, selecting the 13 Provinces of North China as the study area, this study analyzes the spatio-temporal differences and the driving factors. This study found: (1) Between 2006 and 2017, the spatial and temporal differences of GDP in the 13 provinces were statistically significant, with increased total production values and a slowed growth of the industry. In addition, the study area showed an east-west dichotomy in husbandry industry. (2) GDP had shown obvious spatial agglomeration, of which areas with the high production value were in east of Beijing, and areas with low production value were in western Inner Mongolia, Xinjiang and Gansu. (3) Population, animal husbandry output values, numbers of large livestock, and cultivated areas had greatly influenced the GDP of 13 provinces in north China. (4) The three influencing factors on GDP in the 13 provinces were found to be population, animal husbandry output values, and the sizes of cultivated areas. We should synthesize these influencing factors, supplemented with public policy concessions and compensatory measures to develop policies for improving the level of local economic development.